Circular RNA HIPK2 regulates astrocyte activation via cooperation of autophagy and ER stress by targeting MIR124–2HG. Issue 10 (3rd October 2017) - Huang, Rongrong; Zhang, Yuan; Han, Bing; Bai, Ying; Zhou, Rongbin; Gan, Guangming; Chao, Jie; Hu, Gang; Yao, Honghong
ABSTRACT: Circular RNAs are a subclass of noncoding RNAs in mammalian cells; however, whether these RNAs are involved in the regulation of astrocyte activation is largely unknown. Here, we have shown that the circular RNA HIPK2 ( circHIPK2 ) functions as an endogenous microRNA-124 ( MIR124–2HG ) sponge to sequester MIR124–2HG and inhibit its activity, resulting in increased sigma non-opioid intracellular receptor 1 (SIGMAR1/OPRS1) expression. Knockdown of circHIPK2 expression significantly inhibited astrocyte activation via the regulation of autophagy and endoplasmic reticulum (ER) stress through the targeting of MIR124–2HG and SIGMAR1. These findings were confirmed in vivo in mouse models, as microinjection of a circHIPK2 siRNA lentivirus into mouse hippocampi inhibited astrocyte activation induced by methamphetamine or lipopolysaccharide (LPS). These findings provide novel insights regarding the specific contribution of circHIPK2 to astrocyte activation in the context of drug abuse as well as for the treatment of a broad range of neuroinflammatory disorders.